Teaching Learning Materials: The Reviews Coursebooks, Games, Worksheets, Audio Video Files - Sari Dewi, Anak Agung Sagung Shanti (Lingual Journal of Language and Culture, 2016)
Teaching learning materials (TLM) has been widely recognised as one of most important components in language teaching to support the success of language learning. TLM is essential for teachers in planning their lessons, assisting them in their professional duty, and use them as rosources to describe instructions. This writing reviews 10 (ten) teaching learning materials in the form of cousebooks, games, worksheets, and audio video files. The materials were chosen randomly and were analysed qualitatively. The discussion of the materials is done individually by presenting their target learners, how they are applied by teachers and students, the aims of the use of the materials, and the role of teachers and learners in different kind of TLM.
Keywords: TLM, teaching, learning, teachers, students